Effects of late flushing and ewe breed on lamb mortality at birth. - Mohajer, M.; Alimon, Abdul Razak; Naslaji, A. N.; Toghdory, A.; Kamali, R. (Science Explorer Publications, 2013)
A total of 92 Zel and 92 Zel×Shal ewes, 3–5 years of age and body weight of between 35 and 45 kg were randomly allocated in to four groups in order to determine effects of late flushing and breed on lamb mortality at birth. A completely randomized design in factorial arrangement with two factors (Flushing & Breed) and two levels were used. Ewes were fed in two nutritional groups including none flushing diet (2 mcal/kg metabolizeble energy, 11.5 percent crud protein and 1.7 kg/ewe/day dry matter intake) and flushing diet (2.2 mcal/kg metabolizeble energy, 11.5 percent crud protein and 1.7 kg/ewe/day dry matter intake). The flushing continued for last six week of pregnancy. Animals were housed in pens (10 ewes/pen) and allowed free access to water. The results showed that late flushing had a significant effect on lamb mortality at birth (P<0.05). Zel breed had lower lamb mortality than Zel×Shal breed (P<0.05).